Lipid Profile Alterations in Pediatric Patients with Vitamin D Deficiency - Jasmina Katanić; Dejan Dobrijević (Children)
Background/Objectives: Vitamin D deficiency in children has been linked to various metabolic disturbances, including dyslipidemia, which contributes to cardiovascular risk. This study aims to investigate the relationship between vitamin D levels and lipid profiles in children. Methods: A cohort of 332 children with either normal vitamin D or diagnosed vitamin D deficiency was recruited. Serum vitamin D levels were measured, and lipid profiles, including total cholesterol, low-density lipoproteins (LDLs), high-density lipoproteins (HDLs), and triacylglycerols (TAGs), were assessed. The data were analyzed using statistical methods. Results: This study found that children with higher serum vitamin D concentrations had significantly lower TAG (p = 0.033) and very-low-density lipoprotein (VLDL) (p = 0.038) levels and higher HDL levels (p = 0.042), indicating a more favorable lipid profile compared to those with lower vitamin D levels. Conclusions: This study demonstrates that vitamin D deficiency can be associated with dyslipidemia in children. These findings suggest that vitamin D supplementation may be an effective strategy for managing dyslipidemia and reducing cardiovascular risk in pediatric populations. Further research is needed to determine the long-term effects and optimal dosing of vitamin D in this context.